UPLC-TOF-MS/MS-Based Metabolomics Analysis Reveals Species-Specific Metabolite Compositions in Pitchers of Nepenthes ampullaria, Nepenthes rafflesiana, and Their Hybrid Nepenthes × hookeriana - Rosli, Muhammad Aqil Fitri; Mediani, Ahmed; Azizan, Kamalrul Azlan; Baharum, Syarul Nataqain; Goh, Hoe-Han (Frontiers in Plant Science, 2021)
Hybridization is key to the evolution and diversity of plants in nature. Nepenthaceae comprises a family of diverse tropical carnivorous pitcher plant species with extensive hybridization. However, there is no study to date on the metabolite expression of hybrids in this family. We performed a non-targeted metabolomics analysis of the pitchers of two Nepenthes species with different dietary habits, namely the semi-detritivorous N. ampullaria and carnivorous N. rafflesiana with their hybrid (N. × hookeriana) for a comparative study. The whole-pitcher samples were extracted in methanol:chloroform:water (3:1:1) via sonication-assisted extraction and analyzed using ultra-performance liquid chromatography time-of-flight mass spectrometry (UPLC-TOF-MS) followed by data analysis to profile chemical compositions. A total of 1,441 metabolite features were profiled from the three species in which 43.3% of features in the hybrid samples were not found in either of its parents. The partial least squares discriminant analysis (PLS-DA) found 324 metabolite features with variable in projection (VIP) values greater than one in which 55 features were statistically significant. This showed that the hybrid is closer to N. rafflesiana, which is consistent to the previous study on gene and protein expressions. A total of 105 metabolites were putatively identified with manual searches using public metabolite databases. Phenols were detected to be the most abundant secondary metabolites due to a high flavonoid content, especially in N. rafflesiana. The most abundant feature 476.3s:449.102 was found to be the most significant VIP for distinguishing between the three species as a chemical marker. This is the first study comparing metabolites in the carnivory organs of different Nepenthes species with comprehensive profiling and putative identification. The differential metabolite compositions in the pitchers of different species might have ecological implications with the hybrid showing intermediate phenotype between the parents as well as manifesting unique metabolites. However, there is no clear evidence of metabolites related to the differences in dietary habits between the hybrid and the two parent species.